THE EFFECT OF LEADERSHIP STYLE, MOTIVATION AND DISCIPLINE TOWARD EMPLOYEE’S PERFORMANCE - Zulmariad, Randi; Indrayani, Indrayani; Khaddafi, Muammar; wibisono, Chablullah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This research has attempted to explore the influence between leadership styles and motivation of the employee’s performance in services company in Batam. It is found that from the four hypotheses formulation, all hypotheses are accepted because the result shows a positive significant influence. Based on the data analysis, it is revealed that leadership style has a positive influence and significant effect towards employee’s performance. The research proved that the improvement on motivation is significantly influence the employee’s performance. The better a company applied the working discipline also give positive impact towards employee’s performance. Based on the results of the research and discussion, as noted earlier, it can be concluded about the effect of the leadership style, motivation and discipline on the performance of employees at PT. Batamindo Executive Village. Leadership style is the most positive and signiﬁcant effect on the employee performance at PT. Batamindo Executive Village.